SWOT analysis of ways to introduce innovations into agricultural production practices as a prerequisite for searching for promising areas in the field of agroforestry in the Russian Federation - Alexey Тubalov (Hungarian Geographical Bulletin, 2025)
This review aims to collect, analyse and systematize materials on ways to introduce innovations into agricultural production practices. Knowledge and understanding of the features of the mechanisms for introducing innovations allow us to evaluate agroforestry research in terms of its completeness. The basis of the research methodology is the methodological techniques of SWOT analysis. The result of the research is: the establishment of the main ways of introducing innovations into the practice of agricultural production; identifying the strengths and weaknesses inherent in these mechanisms; analysis of opportunities and threats associated with the implementation of innovations through these methods; assessment of the relationship between these tools. The main methods of promoting innovation in the field of agricultural production are: 1) the establishment of an advisory service, 2) the development and implementation of national and regional target programs, and 3) the creation and maintenance of an agroecological service. The identified ways of introducing innovation complement each other. Agroforestry research requires interdisciplinary research to integrate innovations in agroforestry development of territories into a broader agroecological context.